Pengaplikasian Brand Image Rollaas pada Perancangan Interior Galeri Teh di Surabaya - Sriti Mayang, Gabriella Martika Hadi (Intra, 2013)
Tea is one beverage that is very popular and loved by the community. Because besides delicious taste, tea is very good for health. Indonesia is one of the best tea producing country in the world, and 90% with the best quality teas exported abroad. While tea is marketed in Indonesia itself is low quality. Therefore, Rollaas Gallery Tea in Surabaya will help people to get information about tea. Rollaas café is a brand owned by PTPN XII. Rollaas is a café that plant, harvest, and process their own raw materials grain. Rollaas café offers a variety of information and knowledge about all things plantation. In addition, all of the raw materials originating from the menu offered PTPN XII plantation in East Java. Although a domestic product, grain quality is not inferior to foreign products. Ranging from the quality of flavor to a dish display. Expected application of brand image on interior design Rollaas tea gallery in Surabaya can help people to find out various information about tea.